2016
DOI: 10.1093/jb/mvw047
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of paramyosin and thin filaments in the smooth muscle of acorn worm, a member of hemichordates

Abstract: Paramyosin is a myosin-binding protein characteristic of invertebrate animals, while troponin is a Ca-dependent regulator of muscle contraction. Both proteins are widely distributed in protostomes, while in deuterostomes, their distribution is limited; namely, presence of paramyosin and absence of troponin are common features in echinoderm muscles, while muscles of chordates contain troponin but lack paramyosin. In this study, we examined the muscle of a hemichordate, acorn worm, to clarify whether this animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Biochemical analyses suggest the existence of tropomyosin in muscles of a sea lily (Echinodermata) ( Obinata et al. 2014 ) and an acorn worm (Hemichordata) ( Sonobe et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical analyses suggest the existence of tropomyosin in muscles of a sea lily (Echinodermata) ( Obinata et al. 2014 ) and an acorn worm (Hemichordata) ( Sonobe et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…2017 ) genes was observed in circumesophageal muscle of sea urchin, and the function of tropomyosin gene (Sakowv30041361 in supplementary fig. S2 C , Supplementary Material online) is suggested in acorn worm muscle via biochemical analysis ( Sonobe et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like echinoderms, hemichordates have been reported to have no troponin complex 6 . However, TnT and TnC are computationally predicted in the genome of Saccoglossus kowalevskii .…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ signaling, troponin regulation and actomyosin contraction—the input, the mediator, and the output, respectively—are well conserved in almost all bilaterians 3 . However, it has been reported that echinoderms and hemichordates, collectively termed Ambulacraria, lack all components of the troponin complex, which is composed of Troponin-I (TnI), Troponin-T (TnT), and Troponin-C (TnC), thus raising the question of how the troponin systems emerged in the ancestors of bilaterians and how they evolved in the deuterostomes 4 5 6 . One possibility that has been suggested is that Ambulacraria has simply lost the troponin complex and uses another regulatory system, such as direct Ca 2+ binding to myosin 6 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation